Landslide susceptibility mapping based on triggering factors using a multi-modal approach - Kaafarani, Rouba; Abou-Jaoude, Grace; Wartman, Joseph; Tawk, Miriam (MATEC web of conferences, 2019)
Landslide susceptibility mapping has been done using statistical and physically-based assessment techniques with limited focus on mode-specific models to identify failure modes and runout patterns. Because each failure mode has different consequences, it is essential to identify the failure mode associated with each slope inclination category, triggering factor, and geological setting. This paper presents a multimodal regionalscale assessment procedure for rainfall and earthquake-induced landslides, in the country of Lebanon, where landslide inventories are not available. Three failure modes are studied: debris flows, rock-slope failures, and coherent rotational slides. Areas prone to each mode of failure are identified based on geology and topography, then, using mode-specific models, their susceptibility to landslides is assessed. A runout assessment approach is then presented to identify the influence area of each predicted landslide and to obtain comprehensive susceptibility maps. Field assessment validated the proposed model which was in good agreement with actual slope failures across Lebanon. Therefore, the multimodal approach may be used to assess rainfall-induced landslide susceptibility, especially when landslide inventories are unavailable.